Activation of Mechanoreflex, but not Central Command, Delays Heart Rate Recovery after Exercise in Healthy Men - Peçanha, Tiago; de Brito, Leandro Campos; Fecchio, Rafael Yokoyama; de Sousa, Patricia Nascimento; Silva, Natan Daniel; Couto, Patricia Guimaraes; de Abreu, Andrea Pio; da Silva, Giovanio Vieira; Mion, Decio; Low, David A.; de Moraes Forjaz, Claudia Lucia (International Journal of Sports Medicine, 2020)
This study tested the hypotheses that activation of central command and muscle mechanoreflex during post-exercise recovery delays fast-phase heart rate recovery with little influence on the slow phase. Twenty-five healthy men underwent three submaximal cycling bouts, each followed by a different 5-min recovery protocol: active (cycling generated by the own subject), passive (cycling generated by external force) and inactive (no-cycling). Heart rate recovery was assessed by the heart rate decay from peak exercise to 30 s and 60 s of recovery (HRR30s, HRR60s fast phase) and from 60 s-to-300 s of recovery (HRR60−300s slow phase). The effect of central command was examined by comparing active and passive recoveries (with and without central command activation) and the effect of mechanoreflex was assessed by comparing passive and inactive recoveries (with and without mechanoreflex activation). Heart rate recovery was similar between active and passive recoveries, regardless of the phase. Heart rate recovery was slower in the passive than inactive recovery in the fast phase (HRR60s=20±8vs.27 ±10 bpm, p<0.01), but not in the slow phase (HRR60−300s=13±8vs.10±8 bpm, p=0.11). In conclusion, activation of mechanoreflex, but not central command, during recovery delays fast-phase heart rate recovery. These results elucidate important neural mechanisms behind heart rate recovery regulation.
Keywords: exercise pressor reflex; baroreflex sensitivity; cardiovascular control; parasympathetic nervous system; heart rate variability